2020
DOI: 10.1002/jpen.1929
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Smoflipid Therapy: Patient Response and Safety Concerns

Abstract: Background: Intestinal failure-associated liver disease (IFALD) occurs in ≤85% of neonates receiving prolonged parenteral nutrition. Strategies for treatment of IFALD include alternative lipid therapies, such as Smoflipid (Fresenius Kabi). In this study, we reviewed our institutional Smoflipid use, including predictors of patient response and safety concerns. Methods: This is a retrospective chart review of all pediatric patients who received Smoflipid therapy over a 2-year period at Riley Hospital for Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…However, in cases where this is not possible (e.g., short bowel syndrome), decreasing exposure to soybean-based lipid formulations by utilizing alternatives such as SMOFLipid® (Fresenius Kabi USA, Lake Zurich, IL) and Omegaven® (Fresenius Kabi USA, Lake Zurich, IL) is a potential alternative, as these have been demonstrated to have fewer adverse events (30), and can reverse liver injury (31). However, this must be used cautiously, as essential fatty acid deficiency can arise (32). Alternative lipid preparations and PN cycling may prevent or treat PNALD but are not fully effective.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cases where this is not possible (e.g., short bowel syndrome), decreasing exposure to soybean-based lipid formulations by utilizing alternatives such as SMOFLipid® (Fresenius Kabi USA, Lake Zurich, IL) and Omegaven® (Fresenius Kabi USA, Lake Zurich, IL) is a potential alternative, as these have been demonstrated to have fewer adverse events (30), and can reverse liver injury (31). However, this must be used cautiously, as essential fatty acid deficiency can arise (32). Alternative lipid preparations and PN cycling may prevent or treat PNALD but are not fully effective.…”
Section: Discussionmentioning
confidence: 99%
“…Pure sh oil lipid emulsions are considered a treatment that can reverse IFALD, increase survival, and avoid the need for transplantation; thus, they are considered rescue therapy [10]. In contrast, SMOFlipid, which is a mixed lipid emulsion containing soybean oil and sh oil, resolves cholestasis in patients with lower direct bilirubin levels or less severe IFALD [11]. Many researchers have discussed the e cacy of lipid emulsions in SBS patients or SBS animal models; however, there are very few publications on the treatment of IFALD, except for those regarding lipid emulsions.…”
Section: Discussionmentioning
confidence: 99%
“…When PN is required for more than 60 days, IFALD occurs in more than 75% of cases ( 11 ). Although IFALD has a multifactorial origin, it is widely accepted that soy-based lipid emulsions (SO-LEs), used for parenteral nutrition, play a primary pathogenic role due to their high phytosterol content, high ω-6 to ω-3 long-chain polyunsaturated fatty acid ratio, and low levels of α - tocopherol ( 12 ). Whereas IFALD was initially considered as a PN complication, an increasing number of evidence suggests that liver disease is not solely due to PN administration but strongly related to IF factors ( 13 ).…”
Section: Prevalence Etiology and Risk Factorsmentioning
confidence: 99%
“…In 2021, a retrospective study on predictors of cholestasis or IFALD response to SMOF-LE therapy in patients with IFALD showed that 38% of the patients treated with SMOF had cholestasis resolution, 7% improvement, and 45% no response. The responders were older at the beginning of SMOF use, treated with it for longer time, with higher corrected gestational age and lower direct bilirubin levels at the start of treatment ( 12 ). Previous studies had already demonstrated that younger age, increased direct bilirubin, and signs of liver disease were associated with an increased risk of therapy failure.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation